Detailed description regarding the sighting of a Peregrine Falcon submitted by Tim Dwyer - Dwyer, Timothy L.et al (1981)
Tim Dwyer gives a detailed account of his sighting a Peregrine Falcon from Highway 22 west of the Cedar River. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1981. Epson - sheet feed/flatbed